Banking integration and house price comovement - Augustin Landier; David Sraer; David Thesmar (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
The correlation across US states in house price growth increased steadily between 1976 and 2000. This paper shows that the contemporaneous geographic integration of the US banking market, via the emergence of large banks, was a primary driver of this phenomenon. To this end, we first theoretically derive an appropriate measure of banking integration across state pairs and document that house price growth correlation is strongly related to this measure of financial integration. Our IV estimates suggest that banking integration can explain up to one fourth of the rise in house price correlation over this period.
Keywords: G21; F65; R30; 330; Financial Integration; Comovement; House Prices